Answer:
[tex]l_n=3^n-1[/tex]
Step-by-step explanation:
We will prove by mathematical induction that, for every natural n,
[tex]l_n=3^n-1[/tex]
We will prove our base case (when n=1) to be true:
Base case:
As stated in the qustion, [tex]l_1=2=3^1-1[/tex]
Inductive hypothesis:
Given a natural n,
[tex]l_n=3^n-1[/tex]
Now, we will assume the inductive hypothesis and then use this assumption, involving n, to prove the statement for n + 1.
Inductive step:
Let´s analyze the problem with n+1 stones. In order to move the n+1 stones from A to C we have to:
Then,
[tex]l_{n+1}=3l_n+2[/tex].
Therefore, using the inductive hypothesis,
[tex]l_{n+1}=3l_n+2=3(3^n-1)+2=3^{n+1}-3+2=3^{n+1}-1[/tex]
With this we have proved our statement to be true for n+1.
In conlusion, for every natural n,
[tex]l_n=3^n-1[/tex]